Oral manifestations of human immunodeficiency virus/acquired immunodeficiency syndrome and their correlation to cluster of differentiation lymphocyte count in population of North-East India in highly active antiretroviral therapy era - Sarat Kumar Nayak; Bijay Kumar Das; Surya Narayan Das; Namita Mohapatra; Suryakanti Nayak; Lipsa Bhuyan (Wolters Kluwer Medknow Publications, 2016)
Background: The human immunodeficiency virus (HIV) infection which manifests as acquired immunodeficiency syndrome (AIDS) is a disease involving the defects of the T-lymphocyte arm of the immune system. Certain laboratory parameters such as the cluster of differentiation (CD4) count and clinical parameters have long been used as markers of disease progression. In industrialized countries, many studies show a highly correlation between the incidence of oral lesions and immunosuppression and hence, can be used as a marker of immunosuppression. This might not be applicable to a developing country like India. In this study, efforts have been made to supplement the present knowledge on various aspects of oral manifestations in HIV patients in the Indian subcontinent. Aims: To correlate the oral manifestations in HIV/AIDS patients to the level of circulating CD4+ T-lymphocyte count and their effect in anti-retroviral therapy (ART). Subjects and Methods: A total of 104 HIV positive patients were examined for oral lesions. The CD4 count estimated on the same day by fluorescent activated cell sort count machine was then correlated with various oral lesions. Results: Oral manifestations appeared when CD4 count decreased below 500 cells/mm3. Moreover, oral lesions found at different stages showed very strong correlation to their respective CD4 count. Furthermore, there was considerable decline in the incidence of oral manifestations in patients undergoing highly active ART. Conclusions: Oral manifestations are highly predictive markers of severe immune deterioration and disease progression in HIV patients.